Walks with an architect Dubai, Manama, Doha - Guillot, Georges; Terzieff, Catherine; Landmark Films (Virginia : Landmark Media Inc., 2004)
Along the Persian Gulf flourishes a chain of tourists cities with futuristic architecture herealding the look of the 21st century
Title from title screen
DVD format